2014
DOI: 10.1038/bmt.2014.8
|View full text |Cite
|
Sign up to set email alerts
|

In a 12-allele analysis HLA-DPB1 matching is associated with improved OS in leukaemic and myelodysplastic patients receiving myeloablative T-cell-depleted PBSCT from unrelated donors

Abstract: The effect on survival of including HLA-DPB1 in a 12-allele matching strategy was retrospectively evaluated in 130 patients with acute leukaemia and myelodysplasia undergoing T-cell-depleted PBSC transplantation using unrelated donors. Patients received alemtuzumab in vivo T-cell depletion as part of a myeloablative (MA; n ¼ 61) or reduced-intensity conditioning regimen (n ¼ 69). No difference in OS was seen with single-locus mismatching (mm) when 10 conventional alleles (HLA-A, B, C, DRB1 and DQB1) were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…However, an adverse impact of HLA-DPB1 allelic mismatches in both GVH and HVG directions (2 vs 0, RR 1.73, 95% CI 1.09-2.73, P = 0.019, Table 2 and Supplementary Figure 1A) was observed on severe aGVHD III-IV incidence, confirming previous studies. 4,9,15,19,20 This adverse impact of HLA-DPB1 disparities remains also significant (P = 0.01) considering 0+1 vs 2 allelic mismatches (data not shown). Although not significant, a single HLA-DPB1 allelic mismatch results in increased risk of severe aGVHD III-IV (data not shown) underlying a possible dose effect of HLA-DPB1 mismatches.…”
Section: Resultsmentioning
confidence: 82%
“…However, an adverse impact of HLA-DPB1 allelic mismatches in both GVH and HVG directions (2 vs 0, RR 1.73, 95% CI 1.09-2.73, P = 0.019, Table 2 and Supplementary Figure 1A) was observed on severe aGVHD III-IV incidence, confirming previous studies. 4,9,15,19,20 This adverse impact of HLA-DPB1 disparities remains also significant (P = 0.01) considering 0+1 vs 2 allelic mismatches (data not shown). Although not significant, a single HLA-DPB1 allelic mismatch results in increased risk of severe aGVHD III-IV (data not shown) underlying a possible dose effect of HLA-DPB1 mismatches.…”
Section: Resultsmentioning
confidence: 82%
“…A single‐centre UK study of 130 patients transplanted for malignancies demonstrated a trend towards a negative impact of double HLA‐DPB1 mismatching on overall survival in patients otherwise matched for 10/10 HLA loci (HLA‐A, ‐B, ‐C, ‐DRB1, ‐DQB1). This finding was more evident in patients receiving myeloablative conditioning compared with those receiving RIC (Burt et al ., ).…”
Section: Unrelated Adult Donor Selectionmentioning
confidence: 97%
“…Recent literature has suggested that matching at the HLA‐DPB1 locus, in addition to the standard loci, may impact outcomes in ASCT . The β‐chain of the HLA‐DP antigen is known to be highly polymorphic, with 716 alleles encoding 591 proteins and 19 null variants, while the α‐chain has 44 alleles encoding 22 proteins .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Recent literature has suggested that matching at the HLA-DPB1 locus, in addition to the standard loci, may impact outcomes in ASCT. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The β-chain of the HLA-DP antigen is known to be highly polymorphic, with 716 alleles encoding 591 proteins and 19 null variants, while the α-chain has 44 alleles encoding 22 proteins. 27 While many of the HLA genes are in tight linkage disequilibrium (LD), the degree of LD is much lower between HLA-DP and the remainder of the HLA cluster due to a recombination hot spot between the HLA-DQ and HLA-DP loci.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation